Standardized preparation procedure of “thong ake,” a traditional Thai sweetened rice–egg yolk cake, with increased dietary fiber content and reduced sugar content - Juthamas Chamnandee; Chanakan Montatipkul; Nuti Hutasingh; Kanitha Tananuwong (Discover Food)
Abstract The aims of this study were to establish a standardized preparation protocol and develop an improved formula for “thong ake,” a traditional Thai sweetened rice–egg yolk cake. The ingredients of the dessert consisted of blended rice flour and cassava starch (30%), coconut milk (30%), sugar (20%), and egg yolk (20%). The processing procedure comprised preparing sweetened condensed coconut milk and forming a soft dough via prolonged stirring of the warm mixture. In the standardized protocol, the evaporation temperature (70 °C) and total soluble solid of the concentrated sugar–coconut milk (65°Bx) were set. The heating–cooling temperature (55 °C to 75 °C to 55 °C) was developed for dough preparation. Resistant starch type 4 (RS4) and polyol were fortified to enhance dietary fiber and reduce the sugar content of the dessert, respectively. Up to 10% RS4 substitution of native starch/flour resulted in a decrease in the hardness, chewiness, and gumminess of the dessert (p < 0.05). However, the overall acceptance score of the 10% RS4 formula was not different from that of the control (p ≥ 0.05). This formula was selected for developing the reduced sugar version of the dessert, in which 25% sucrose was replaced by xylitol, maltitol, or sorbitol. RS4 and polyol had a slight effect on the dessert’s moisture content, aw, and color. However, that ingredient combination further decreased the hardness, chewiness, and gumminess of the dessert (p < 0.05). The formula with 10% RS4 and 5% sorbitol obtained an overall consumer acceptance score similar to that without polyol (p ≥ 0.05) and had the lowest ingredient cost. This most suitable formula yielded a dessert with 8.15% dietary fiber and 25% sugar reduction. The standardized protocol and improved formulation of thong ake used in this study could enhance quality control and the nutritional profile of the dessert.